A single-center cost analysis assessing a change in vasopressin formulation. (4th April 2021) - Kelly, Courtney E; Miller, Christopher; Darko, William; Cwikla, Greg; Mogle, Bryan; Featherly, Julianna; Marcinak, Rebecca; Probst, Luke A; Seabury, Robert
Abstract: Purpose: Cost savings achieved at an academic medical center by reformulating the institution's standard vasopressin infusions to reduce waste are described. Summary: After a retrospective review of vasopressin utilization over a 4-month period revealed that only approximately 40% of dispensed vasopressin units were actually administered to patients, pharmacy leaders determined that the institution's standard vasopressin concentration for continuous infusions (100 units in 100 mL of sodium chloride 0.9% injection) was resulting in substantial waste, as many infusion preparations were not needed within the 18- to 24-hour expiration window. A concentration of 20 units/100 mL was adopted as the new standard formulation for vasopressin continuous infusions, with use of alternative concentrations allowed on a restricted basis. A pre-post study to assess the impact of the formulation change indicated a 38.7% decrease in vasopressin utilization (from 21, 900 to 8, 480 units) relative to utilization in a retrospective sample of patients who received vasopressin infusions prior to the formulation change. This reduced utilization equated to a cost decrease of $55, 656.20 (as calculated on the basis of 2017 cost estimates) or $77, 214.23 (as calculated on the basis of 2019 cost estimates) for the time period collected. It was estimated that the new formulations could yield annual cost savings ranging from $222, 625 to $308, 857. Conclusion: To our knowledge, this is the first description of cost savings following a change in formulation of vasopressin for continuous infusions. Other institutions could consider employing a similar approach in addition to the previously reported cost-saving interventions, such as lower vasopressin starting doses and vasopressin restriction policies.